How to Work on a Non-endangered Species and Contribute to Cetacean Conservation: An Example by the Sarasota Dolphin Research Program - Gulland, Frances M. D. (Frontiers in Marine Science, 2021)
The world’s most endangered small cetaceans are found in countries many miles from Sarasota Bay and its common bottlenose dolphins (Tursiops truncatus). Information on the ecology and threats to many of these endangered cetaceans is often far more limited than that on bottlenose dolphins, with the IUCN Red Data List describing many species as “data deficient.” In many developing nations where these rare species occur, resources for research and monitoring are scant, and logistical challenges further limit research into marine mammal health and population status and their threats. The Sarasota Dolphin Research Program (SDRP) has tackled this problem by using the bottlenose dolphin as a model for cetacean species in other parts of the world and using its resources to assist scientists working with more endangered species of cetacean. The celebration of 50 years of study by the SDRP exemplifies how using long-term data on known individuals can advance the fields of cetacean behavior, ecology, life history, physiology, toxicology, and medicine, all providing information for informing certain conservation actions. The Sarasota team has used their work to inform conservation policy both home and abroad.